Janus Quasi-Solid Electrolyte Membranes with Asymmetric Porous Structure for High-Performance Lithium-Metal Batteries - Chen, Zerui; Zhao, Wei; Liu, Qian; Xu, Yifei; Wang, Qinghe; Lin, Jinmin; Wu, Hao Bin (Nano-Micro Letters, 2024)
Quasi-solid electrolytes (QSEs) based on nanoporous materials are promising candidates to construct high-performance Li-metal batteries (LMBs). However, simultaneously boosting the ionic conductivity (σ) and lithium-ion transference number (t+) of liquid electrolyte confined in porous matrix remains challenging. Herein, we report a novel Janus MOFLi/MSLi QSEs with asymmetric porous structure to inherit the benefits of both mesoporous and microporous hosts. This Janus QSE composed of mesoporous silica and microporous MOF exhibits a neat Li+ conductivity of 1.5 × 10–4 S cm−1 with t+ of 0.71. A partially de-solvated structure and preference distribution of Li+ near the Lewis base O atoms were depicted by MD simulations. Meanwhile, the nanoporous structure enabled efficient ion flux regulation, promoting the homogenous deposition of Li+. When incorporated in Li||Cu cells, the MOFLi/MSLi QSEs demonstrated a high Coulombic efficiency of 98.1%, surpassing that of liquid electrolytes (96.3%). Additionally, NCM 622||Li batteries equipped with MOFLi/MSLi QSEs exhibited promising rate performance and could operate stably for over 200 cycles at 1 C. These results highlight the potential of Janus MOFLi/MSLi QSEs as promising candidates for next-generation LMBs. Highlights: 1 Janus quasi-solid electrolyte membranes with asymmetric porous structure were constructed, showing a high σLi+ of 1.5 × 10-4 S cm-1 and a high t+ of 0.71. 2 The solvation structures and ion transport dynamics in nanopores have been deciphered, manifesting a concentrated electrolyte-like structure and regulated transport behaviors. 3 Quasi-solid NCM 622||Li cells have been demonstrated to stably cycle for 200 cycles at 1 C, and pouch cell has shown high tolerance for abuse.